MENINGKATKAN DAYA BACA SISWA MELALUI POJOK BACA DI SMP - Yolanda, Feza Herli; Atmaja, Loliek Kania; Manjato, Ajat; Rustinar, Eli; Kusumaningsi, Dewi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Reading corners can be used to increase students' interest in reading. This research aims to improve students' reading ability through reading corners in junior high schools. What is contained in this research is how effective the reading corner is in increasing students' reading interest. What is the school doing to prepare for the reading corner movement in the classroom? What are the problems behind students' low interest in reading? This research is a qualitative descriptive study. This research uses data collection techniques, namely interviews, observation techniques, data reduction, data presentation. The techniques for checking the validity of the data used in this research are observation and interviews. There are several factors that influence improving students' reading ability through reading corners in junior high schools, namely having a reading corner in each class makes students more enthusiastic about reading books, and the reading corner in each class is made as attractive as possible.